CELEB trial: Comparative Effectiveness of Lung volume reduction surgery for Emphysema and Bronchoscopic lung volume reduction with valve placement: a protocol for a randomised controlled trial. Issue 10 (17th October 2018) - Buttery, Sara; Kemp, Samuel V; Shah, Pallav L; Waller, David; Jordan, Simon; Lee, John T; Banya, Winston; Steiner, Michael C; Hopkinson, Nicholas S
Abstract : Introduction: Although lung volume reduction surgery and bronchoscopic lung volume reduction with endobronchial valves have both been shown to improve lung function, exercise capacity and quality of life in appropriately selected patients with emphysema, there are no direct comparison data between the two procedures to inform clinical decision-making. Methods and analysis: We describe the protocol of the CELEB study, a randomised controlled trial which will compare outcomes at 1 year between the two procedures, using a composite disease severity measure, the iBODE score, which includes body mass index, airflow obstruction, dyspnoeaand exercise capacity (incremental shuttle walk test). Ethics and dissemination: Ethical approval to conduct the study has been obtained from the Fulham Research Ethics Committee, London (16/LO/0286). The outcome of this trial will provide information to guide treatment choices in this population and will be presented at national and international meetings and published in peer-reviewed journals. We will also disseminate the main results to all participants in a letter. Trial registration number: ISRCTN19684749 ; Pre-results.